Comparison of natural crosslinking agents for the stabilization of xenogenic articular cartilage. Issue 6 (18th December 2015) - Pinheiro, Amanda; Cooley, Avery; Liao, Jun; Prabhu, Rajkumar; Elder, Steven
ABSTRACT: Osteochondral xenografts are potentially inexpensive, widely available alternatives to fresh allografts. However, antigen removal from xenogenic cartilage may damage the extracellular matrix and reduce compressive stiffness. Non‐crosslinked xenogenic cartilage may also undergo rapid enzymatic degradation in vivo. We hypothesized that natural crosslinking agents could be used in place of glutaraldehyde to improve the mechanical properties and enzymatic resistance of decellularized cartilage. This study compared the effects of genipin (GNP), proanthocyanidin (PA), and epigallocatechin gallate (EGCG), on the physical and mechanical properties of decellularized porcine cartilage. Glutaraldehyde (GA) served as a positive control. Porcine articular cartilage discs were decellularized in 2% sodium dodecyl sulfate and DNase I followed by fixation in 0.25% GNP, 0.25% PA, 0.25% EGCG, or 2.5% GA. Decellularization decreased DNA by 15% and GAG by 35%. For natural crosslinkers, the average degree of crosslinking ranged from approximately 50% (EGCG) to 78% (GNP), as compared to 83% for the GA control. Among the natural crosslinkers, only GNP significantly affected the disc diameter, and shrinkage was under 2%. GA fixation had no significant effect on disc diameter. Decellularization decreased aggregate modulus; GA and GNP, but not EGCG and PA, were able to restore it to its original level. GNP, PA, and GA conferred a similar, almost complete resistance to collagenase degradation. EGCG also conferred substantial resistance but to a lesser degree. Overall, the data support our hypothesis and suggest that natural crosslinkers may be suitable alternatives to glutaraldehyde for stabilization of decellularized cartilage. © 2015 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 34:1037–1046, 2016.